Ta'tsîru Kafâati Mihniyyah Mudarrisi al-Lughah al-Arabiyah li Tarqiyati Mahârati al-Kitâbah li at-Thullâb bi Madrasati ad-Dîniyyah at-Takmîliyyah al-Awwaliyyah Sunan Kalijaga Kebun Jati Larangan Pamekasan - Thayyibah Thayyibah (IAIN Madura, 2020)
This paper discusses the competence of an Arabic teacher to improve student writing skills in Madrasah Diniyah Takmiliyah Sunan Kalijaga, Kebon Jati, Larangan, Pamekasan. This study aimed to determine the extent of the influence of professionalism of an Arabic teacher in improving student's writing skills. In this study, the researcher used a quantitative method. While the process, the researcher has a source of data in the form of Imla learning process as well as the students involved in it. The method used to display the data is through questionnaires, observation, documentation, and interviews. The results of this study prove that teacher professionalism has an influence on improving student’s writing skills with a value of 0.321, the value is between 0.200 to 0.400 with a low interpretation.